MEKANISME AKSES NELAYAN DALAM AKTIVITAS ILLEGAL FISHING DI DANAU TEMPE - Tubangsa, Ian (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2022)
This study describes the access mechanism of fishermen involved in illegal fishing activities in Lake Tempe. The purpose of this research is to explain the forms of fisherman's access and the biophysical factors that support fishermen's access in the practice of illegal fishing. This research used a qualitative approach. Informants were determined using the Snowball method. Data were collected by using technique of indept intervew, participant observation, and documentation. The results of the study show that: 1) rights-based access mechanisms are obtained through cooperation with fishing area owners; 2) structural and relational-based access mechanisms are obtained through relations with capital owners, law and government officials, and social identities; and 3) water level conditions of the lake make it easier for fishermen to access illegal fishing practices and make it difficult to supervise. For this reason, fishery resource management planning in Lake Tempe is needed by considering social and environmental conditions through collaboration between fishermen and the government.